METHOD IMPROVEMENT FOR DETERMINING THE TECHNICAL LEVEL OF CIVIL AIRCRAFT - V. V. Efimov; K. O. Chernigin (Научный вестник МГТУ ГА, 2017)
Aircraft are high-tech engineering products which are characterized by a wide range of properties including the two most important groups that respectively characterize the efficiency and technical level.Improving the aircraft efficiency is an essential factor for air transport development, but the efficiency can not be fully describe the technical system, especially in forecasting and new technology requirements development. Aircraft designer must evaluate the prospects of a technical solution, but it’s not always possible to calculate the efficiency accuratelyat the design stage. The operator should be able to choose the most technically-advanced aircraft available in the market inorder not to let it grow obsolete quickly. This determines the need for non-economic evaluation of technical systems that can be done by assessment of their technical level.The technical level is a general index that includes a set of technical perfection indicators. Technical perfection is reflected in terms of material and energy intensity, in terms of ergonomics, safety, etc. and is achieved as a result of original design solutions, the use of new high-strength low-density materials, the introduction of advanced technological pro-cesses, calculation methods, verification, testing, etc.There is a tight connection between the product properties and its weight, because weight is the material reflection of these properties. Therefore, improvement of the product properties usually leads to an intense increase of its weight. To deal with this phenomenon is only possible with widely using scientific and technical progress results. In accordance with this, the technical perfection can be interpreted as a major component of quality that is created without the weight increase. This approach requires investment in research and testing new technical solutions.The method was developed to determine the technical level of civil long-haul aircraft which has been modified to incorporate features of general aviation aircraft operation. However, according to the authors of this article, this method requires some clarification. This is the subject of this article where the technical level generalized index equation is refinedand with the use of which the technical level of civil long-range aircraft is determined.